Zdalna terapia mowy w opinii logopedów - Dolińska, Dominika (Studia Edukacyjne, 2023)
The article presents the findings of a study that aimed to explore the opinion of speech therapists regarding remote speech therapy. The study was conducted between January and March of 2023 and the data was collected through a quantitative method via a diagnostic survey. The sample comprised 62 speech therapists with varying levels of work experience and geographical locations. The outcomes indicated that speech therapists generally held a negative opinion of remote speech therapy, perceiving it as more problematic and limiting than beneficial. Most respondents had not participated in online training or courses aimed at improving their qualifications in remote speech therapy, which could potentially influence their attitudes towards it. The study suggests the need to develop and share practical tips on remote speech therapy to better prepare specialists for a possible transition to remote modes of service delivery.